A Rare Arrhythmia in a Child with Atrial Fibrillation: Ashman Phenomenon - Gülhan Atakul; Ferhat Sarı; Rana İşgüder; Gökhan Ceylan; Özlem Saraç Sandal; Yakup Ergül; Murat M. Yılmazer; Hasan Ağın (Galenos Yayinevi, 2019)
Ashman phenomenon is an aberrant ventricular conduction seen in atrial fibrillation. It is due to a change in the length of QRS complex. It is most often mistaken for a premature ventricular contraction (PVC) or ventricular tachycardia. A 15-year-old male patient was admitted to the emergency department with the complaint of palpitation. He had a 3-year history of type 1 diabetes mellitus and he was using isotretinoin for nodular acne for 1 month. His heart rate was 195 beats/min and his electrocardiographic findings were compatible with supraventricular tachycardia (PVC). Adenosine was administered as an intravenous push twice, however, since atrial fibrillation did not return to normal sinus rhythm , he was transferred to our pediatric intensive care unit. After a transesophageal echocardiography showing no thrombus or structural defect, synchronized cardioversion was attempted at escalating doses of 0.5 J/kg, 1 j/kg and 1.5 j/kg dose, but the patient was unresponsive. After the cardioversion, the patient did not return to normal sinus rhythm hence re-evaluated with ECG again. Persisted tachycardia, absence of p waves, similar extra-ventricular beats and unequal R-R distances were observed. This rhythm was found to be compatible with atrial fibrillation and that the supraventricular pulses delivered with the accompanying aberration were Ashman's phenomena. After infusion of 3 mg/kg, amiodarone was continued 6 mcg/kg/min as maintenance infusion. His rhythm went back to normal. Amiodarone infusion was discontinued at the 48th hour and the patient was transferred to pediatric cardiology service with oral propranolol treatment. The Ashman phenomenon is a very rare condition in childhood and should be distinguished from the series of PVC and sequentially identified supraventricular complexes, due to completely different treatment options.